2008
DOI: 10.1021/jp801938w
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Novel Glucose Biosensor Based on a Highly Electroactive Polystyrene/Polyaniline/Au Nanocomposite

Abstract: A novel nanocomposite with a core-shell structure containing polystyrene (PS), polyaniline (PANI), and Au nanoparticles (NPs) was synthesized. The nanocomposite was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared spectroscopy (FTIR). Cyclic voltammetric experiments indicated that the nanocomposite had excellent redox ability in a wide range of pH values. The existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 44 publications
0
71
0
1
Order By: Relevance
“…PANI 与 AuNP 比较常见的复合形式是核壳 结构的纳米复合物, 例如以聚苯乙烯(PS)为核, PANI 和 AuNP 为壳的 PS/PANI/AuNP 纳米复合物 [80] ; 或者以 AuNP 为核, PANI 为壳的 AuNP/PANI 纳米复合物 [81] ; 或 者是 PANI/AuNP 中空微球纳米复合物 [82] 等 . 这些 PANI/AuNP 纳米复合物, 由于 AuNP 的引入电导率明显 提高, 促进了 PANI 的电荷转移过程, 其修饰电极均表 现出在中性环境下的高电化学活性.…”
Section: 金纳米粒子复合unclassified
“…PANI 与 AuNP 比较常见的复合形式是核壳 结构的纳米复合物, 例如以聚苯乙烯(PS)为核, PANI 和 AuNP 为壳的 PS/PANI/AuNP 纳米复合物 [80] ; 或者以 AuNP 为核, PANI 为壳的 AuNP/PANI 纳米复合物 [81] ; 或 者是 PANI/AuNP 中空微球纳米复合物 [82] 等 . 这些 PANI/AuNP 纳米复合物, 由于 AuNP 的引入电导率明显 提高, 促进了 PANI 的电荷转移过程, 其修饰电极均表 现出在中性环境下的高电化学活性.…”
Section: 金纳米粒子复合unclassified
“…( Yang, Cao, & Tan, 2014) To solve the problem, many different approaches have been attempted, and a significant attempt to overcome these drawbacks is that using sulfonated polystyrene (SPS) microspheres as substrates to prepare SPS/PANI composites. ( Liu et al, 2008) Using SPS microspheres as substrates can significantly improve the processability of PANI as well as reduce aggregation of PANI because SPS is similar to amphiphilic polymer. ( Dai et al, 2011) In addition, the incorporation of silver (Ag) nanoparticles in PANI can obviously promote the anticorrosive properties of PANI because Ag nanopaiticles exhibit excellent environmental stability and anticorrosive properties.…”
Section: Introductionmentioning
confidence: 99%
“…12 Tian et al have prepared polyaniline-gold nanoparticles multilayer lms by layer by layer method and showed that sensor can be used with very good electroactivity in a neutral pH environment. 13 Feng et al also have described the Au-PANI matrix to construct sensor and has showed the sensor is having high catalytic activity and enhanced detection sensitivity.…”
Section: Introductionmentioning
confidence: 99%